Μικροβιολογική ποιότητα νωπού αγελαδινού γάλακτος:οριζόντια δειγματοληψία από ένα βουστάσιο - Κυπριανού, Κυριακή (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
The microbiological quality of raw cow's milk is influenced by many factors. Important factors are the hygiene conditions in the farm and the specific conditions during milking, transport and cooling of milk. Subclinical mastitis can also affect the microbiological quality of the milk. The objective of this study was to analyze 38 samples, 37 samples from individual animals andthe Bulk Tank milk (BTM) sample of a specific farm. All samples were collected from the dairy farm under the same conditions and were examined for a total of four different microbiological parameters; (i) Total Viable Count (TVC), (ii) Enterobacteriaceae, (iii) ESBL and (iv) MRSA. The results showed that the TVC of the BTM sample was within the legal limit of <100,000 cfu/ml at 4,7log10 cfu/ml. TVC results from the individual animals ranged from 4,8 log10 cfu/ml to 7,4 log10 cfu/ml. A total of 86% of the samples were positive for Enterobacteriaceae with numbers ganging from 2,7 log10 cfu/ml to5,8 log10 cfu/ml. ESBL Enerobacteriaceae were isolated from a total of 54% of the samples and MRSA from 59%. The results demonstrated that there were significant differences in the microbial quality between animals within the same farm. Therefore, better hygienic conditions alongside with better milking practices are recommended which will improve themicrobial quality of the milk from individual animals and reduce the microbial numbers in the BTM.
Keywords: Microbiological; Milk